The Role of the Organization of American States in Peaceful Settlement of Disputes. - Boulos, Sonia (Iuris Dictio, 2017)
This article analyzes the role of the OAS in creating political frameworks for the peaceful settlement of the disputes, and its role in enhancing the adjudicative frameworks for settling disputes arising between American states. The article suggests that while the OAS had succeeded in creating strong political frameworks for the peaceful resolution of regional conflicts, it was not equally successful in enhancing the normative framework needed for the legal settlement of conflicts between American States.